Influence of sodium aluminate on calcium leaching of shotcrete in tunnels - Ye, Fei (Pergamon-Elsevier Science Ltd, 2021)
Road tunnels built in water-rich areas are prone to calcium leaching owing to long-term erosion by groundwater, which results in calcite deposition in tunnel drainage system. Calcite deposition can lead to the clogging of drainage pipes and water gutters. When these facilities are blocked, the groundwater behind the tunnel lining cannot be discharged in time, which will cause the increase of water pressure and seriously jeopardizes the stability of the concrete lining. Therefore, it can be seen that calcite deposition in tunnels is an urgent problem to be addressed. This research aims to analyse the causes of calcite deposition and to use sodium aluminate set accelerator as an object of study to investigate its effect on calcite deposition. In order to achieve this, an apparatus was developed to study the calcium leaching process in shotcrete and a mathematical model was developed to solve for the changes in calcium ions concentration during the calcium leaching process. By comparing the experimental results with the results of the mathematical model, the effect of sodium aluminate set accelerator on calcium leaching of shotcrete was analysed comprehensively. Results showed that the calcium in calcite is derived from the cement in shotcrete. Sodium aluminate affects the saturation concentration of Ca (OH)2 and C-S-H in the liquid phase and the crystallization of Ca(OH)2 and C-S-H in the solid phase. And a low dosage of sodium aluminate accelerates calcium leaching, thereby deteriorating the leaching resistance of shotcrete. Conversely, a high dosage of sodium aluminate inhibits calcium leaching, thereby enhancing the leaching resistance of shotcrete.